Power and Praxis Writing and Performance in Megillat Ahimaatz - Lieber, Laura Suzanne 1972- (2023)
In this essay, the text of Megillat Ahimaatz offers a window into compositional conventions, particularly around liturgy, as well as understandings of writing at a pivotal moment, and in a pivotal location: southern Italy (Apulia) in during the 9th-11th centuries. Both writing technologies and ritual performances (liturgical and magical) occupy prominent places in Megillat Ahimaatz, and the text seems to reflect a moment of great cognizance concerning the significance of writing and performative power and praxis, particularly among Jews but also in other communities, as well, as viewed through Jewish eyes. In this essay, I will (1) outline the text's general interest in writing, writers, performers, and performance, after which I will (2) present the specific varieties of writing and performance that occur in Megillat Ahimaatz. Finally, I will (3) examine the scroll's specific vocabulary for writing (texts and practices) and similarly, I will consider the way liturgical performance is described. These elements - narrative and lexical - when read together offer a window into at least one writer's understanding of his tradition at a pivotal crossroads in Jewish literary and liturgical history.